2023
DOI: 10.4236/ojas.2023.131012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Desmodium uncinatum</i> Leaf Meal in the Diet on Lohmann Brown Hens’ Laying Performance and Eggs Quality

Abstract: A cheap, safe and available alternative protein source to soybean is a huge priority for the developing world. This study is aimed at evaluating the effects of Desmodium uncinatum leaf meal incorporation levels in the diet on Lohmann Brown hens' laying performances. For this purpose, 60 Lohmann Brown hens aged 33 weeks with an average weight of 1.78 kg were randomly assigned to 3 treatment groups of 20 birds each with 4 replicates. The experimental treatments consisted of DULM 0 , DULM 5 , and DULM 10 containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
0
2
Order By: Relevance
“…In our study, there was no mortality during the trial. The lack of effect of the diet on laying hens weight has already been demonstrated [8,19], in contrast with our study on guinea fowls fed diets supplemented with hevea seed meal [3].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, there was no mortality during the trial. The lack of effect of the diet on laying hens weight has already been demonstrated [8,19], in contrast with our study on guinea fowls fed diets supplemented with hevea seed meal [3].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the findings of Syahruddin et al [24] in our study there was a decrease in laying rate when the levels of supplementation with hevea seed meal was increased. However, there was an increase of laying rate when levels of supplementation with Desmodium leaf flour increased which is contrary to results presented by Kuietche et al [8] who used diets supplemented with Desmodium uncinatum and found a decrease of laying rate with the increase of the level of the plant. However, the plant used in their study Desmodium uncinatum is not similar to the plant Desmodium tortuosum used in the present study;…”
Section: Discussioncontrasting
confidence: 95%